Morphological Variations among the Different Populations of Estuarine Croaker (Pseudotolithus elongatus) in the Cross-River Estuary, Nigeria - E., Essien, Eyo; P., Inyang-Etoh, Aniema; U., Eteng, Sunday; J., Odum, Caroline (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
This study examines the morphological variation of the estuarine croaker (Pseudotolithus elongatus) in the Cross River Estuary, Nigeria, to understand how environmental factors shape fish populations. A total of 815 fish specimens were collected from five stations along the estuary, representing diverse salinity gradients and levels of anthropogenic influence. Morphometric analysis focused on 11 key body traits, adjusted for size using allometric scaling. Principal Component Analysis (PCA) revealed that the first component (PC1) accounted for 91.58% of the total variance, capturing the majority of morphological variation. Discriminant Function Analysis (DFA) further identified three distinct morphological groups, with an overall classification accuracy of 61.44%. Monte Carlo simulations indicated that sampling variability could impact observed morphological distinctions, particularly at sites with minor environmental differences. Findings underscore the role of environmental gradients in driving morphological diversity and suggest the need for refined sampling protocols and classification models to improve species differentiation in estuarine ecosystems. The study recommends managing the croaker population as distinct stocks based on local environmental conditions to support effective conservation, thereby sustaining population diversity and resilience in the estuary.